Comparative evaluation of the effect of topical fluorides on the microhardness of various restorative materials: An in vitro study - Gill N; Pathak A (Wolters Kluwer Medknow Publications, 2010)
Context: Topical fluorides can recharge the fluoride content of exhausted glass ionomer cements, converting them into fluoride reservoirs. However, the high reactivity of fluoride agents used in topical fluorides may result in the deterioration of surface properties of these restorations. Aim: To evaluate and compare the effect of topical fluorides on the microhardness of conventional glass ionomer cements (Fuji II,GC Corporation,Tokyo, Japan and Ketac Fil Plus,3M ESPE, Seefeld, Germany), high viscosity conventional glass ionomer cements (Ketac Molar Easymix, 3M ESPE, Seefeld, Germany and Fuji IX GP, GC Corporation, Tokyo, Japan), and resin-modified glass ionomer cements (Vitremer, 3M ESPE, St.Paul, MN, USA and Fuji II LC, GC Corporation, Tokyo, Japan). Materials and Methods: Twenty-one pellets were made of each material and stored in distilled water at 37°C for 48 h. These were then randomly divided into 3 subgroups of 7 pellets each. One subgroup was treated by 4 min application of 1.23% acidulated phosphate fluoride (APF) gel, other subgroup with 2% sodium fluoride (NaF) gel, and the third subgroup was used as control. Thereafter, all the pellets were subjected to microhardness testing (load = 100 g for 15 s). Results: APF gel of 1.23% produced a statistically significant decrease in microhardness (P<0.05) of all the restorative materials as compared with restorative materials used as control. The decrease in the microhardness was more pronounced in conventional glass ionomer cements and least pronounced in resin-modified glass ionomer cements. No statistically significant difference (P > 0.05) in microhardness was found after NaF treatment in all the restorative materials tested as compared with control subgroups. Conclusion: The use of 1.23% APF gel may be detrimental to the long-term durability of glass ionomer restorations.